SUPPLY CHAIN INTEGRATION AND GLOBAL TREND RESPONSIVENESS STUDY OF UNIQLO’S MARKETING STRATEGY - Siti Rivana; Faraa Zashika; Ar'Rachma Frischa Fauziah (Integrative Perspectives of Social and Science Journal, 2026)
This study examines the relationship between Supply Chain Integration (SCI) and Global Trend Responsiveness (GTR) in supporting Uniqlo’s global marketing strategy. Using a qualitative approach through literature review, media analysis, and case study methods, the study explores how operational integration contributes to the company’s ability to respond to changing consumer preferences and global market trends. The findings indicate that an integrated supply chain enhances information flow, operational flexibility, and decision-making speed, enabling Uniqlo to adapt effectively to dynamic market conditions. Furthermore, the integration of digital technology and omnichannel strategies strengthens the company’s responsiveness to global trends and consumer demands. The study concludes that the synergy between SCI and GTR serves as a critical factor in sustaining Uniqlo’s competitive advantage and reinforcing its position in the global fashion industry.